The intensity of the religious attitude of Christians in Poland - personality and education - Kopaniecka, Agata; Karakiewicz, Beata (Journal of Education, Health and Sport, 2022)
Introduction: Christianity, like any religion, plays the role of providing spiritual help and sets out rules that are considered moral or immoral. Due to individual personality differences, everyone has a different way of coping with the fear of the consequences of sin. Are there people professing Christianity who react with a neurotic attitude and suffer from ecclesiogenic neurosis, i.e. disorders caused by the dogmatism of the Church, really common? The attention was paid to the level of education in relation to the intensity of the religious attitude. This study aims to bring closer the topics of neuroticism, agreeableness, and related education to the intensity of the religious attitude. In addition, the results of the study will be discussed in the discussion. Aim of the study: Determining the relationship between the intensity of religious attitude and personality and education of Christians in Poland. Materials and methods: The research group consisted of 132 people over 15 years of age professing Christianity in Poland, including 108 women and 24 men. The average age of the participants in the study was 25 years. The youngest respondent was 16 years old, and the oldest 60 years old. The study was conducted using a demographic survey and standardized research tools: the Religious Attitude Intensity Scale (SIPR) and NEO-FFi by Costa and McCrae. Results: In the examined group professing Christianity, high intensity of religious attitude did not have a statistically significant influence on the intensity of neuroticism and agreeableness. Moreover, high education is not related to the low intensity of religious attitude.